L05 Huntexil (pridopidine) improves voluntary motor function in patients with Huntington's disease: results from the phase 3 study MermaiHD. (16th November 2010) - Squitieri, F; Landwehrmeyer, G B; Garcia de Yebenes, J; Reilmann, R; Rosser, A; Sword, A; Rembratt, Å; Tedroff, J
Abstract : Background: Pridopidine is a dopaminergic stabiliser, a new class of compound that stabilises the dopamine system and has the potential to treat neurological and psychiatric disorders characterised by altered dopamine transmission. Aims: To investigate the efficacy and safety of pridopidine in patients with Huntington's disease (HD). Methods: MermaiHD was a 6 month randomised, double blind, placebo controlled European study. Eligible patients were aged ≥30 years with a score of ≥10 points in the modified motor score (mMS) at screening. The mMS is a validated subscale of the UHDRS total motor score (UHDRS-TMS) equal to the UHDRS-TMS excluding eye movements, dystonia and chorea. Patients were randomised 1:1:1 to pridopidine 45 mg once or twice daily or placebo. The primary outcome was effect of treatment on voluntary motor function (mMS). Results: After 26 weeks pridopidine 45 mg twice daily improved the mMS by 0.99 points (full analysis set (FAS), n=437; p=0.042 vs placebo; NS after adjustment for multiplicity). After adjusting for CAG repeats, the mMS change from baseline with pridopidine 45 mg twice daily was −1.20 points vs placebo (FAS, n=393; p=0.019). Pridopidine 45 mg twice daily significantly improved the UHDRS-TMS (change from baseline −2.96 points; FAS, n=437; p=0.004 vs placebo) with improvements in eye movements and dystonia subdomains (not chorea). With placebo, the regression coefficients for CAG repeats versus rate of motor symptom progression was significant (p=0.0051; 0.3 points on the mMS per CAG repeat after 26 weeks). The regression coefficients were not significant with pridopidine. Effects were similar regardless of whether patients were taking neuroleptics. Pridopidine was well tolerated and had an AE profile similar to placebo. Conclusions: This study suggests a beneficial effect of pridopidine 45 mg twice daily on motor function in patients with HD. A possible effect on motor symptom progression as suggested by changes in the mMS per CAG should be studied further.